PETROLOGY OF PERIDOTITES FROM THE OPHIOLITE MELANGE IN CAPE POVOROTNY, TAIGONOS PENINSULA, NE RUSSIA: MANTLE PROCESSES BENEATH A SUBDUCTION ZONE - Bazylev B.A.; Palandzhjan S.A.; Ganelin A.V.; Ishiwatari A.; Dmitrenko G.G.; Silantyev S.A. (My University, 2001)
Mineralogical and geochemical evidence indicates that peridotites of the ophiolite complex (spinel lherzolites, spinel harzburgites, dunites, and wehrlites) in Cape Povorotny were produced during a single magmatic episode in a suprasubduction geodynamic environment. As follows from the composition of the peridotites, the magmatic process was characterized by the melting of mantle material in a system open to the introduction and removal of the melt. The assayed composition of the introduced melt is noted for a strong enrichment in REE, low HREE concentrations, and significant minima at Nh, Zr, and Ti. The composition of the melt corresponded to the probable composition of the melt derived from the subducted plate.